Effect of high pressure homogenization on lactic acid bacteria phages and probiotic bacteria phages - Capra, María Luján (2009)
To study the effect of high-pressure homogenization on virus inactivation, phages specific for Lactobacillus delbrueckii, Lactobacillus helveticus, Streptococcus thermophilus, Lactococcus lactis, Lactobacillus paracasei and Lactobacillus plantarum were assayed. Influence of pressure level, cycle number, suspension medium and phage concentration were studied at 25ºC. Viability reductions were proportional to pressure and cycle number, though inactivation extent was phage dependent. At 100 MPa, some bacteriophages were completely inactivated (6 log10 reduction) after 3 or 5 cycles, while others remain infective after 8 cycles. For all phages, 60 MPa were insufficient for complete inactivation even after 8 cycles. No clear influence was observed regarding media tested. Inactivation seems to depend on phage concentration: the highest the initial load, the biggest the reduction achieved. Although our results show that several studied phages are resistant to dynamic high pressure, this strategy could be combined with others aiming to control their presence in raw milk.